2001
DOI: 10.1021/es0106568
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Photocatalytic Activity of TiO2−Polyoxometalate Systems

Abstract: The present study reports the investigation of polyoxometalate catalyzed electron transfer from the conduction band of photoexcited TiO2 to molecular oxygen. The oxidation of 1,2-dichlorobenzene (DCB) was used as an index reaction for evaluating the photocatalyst systems TiO2-PW12O40(3-), TiO2-SiW12O40,4- and TiO2-W10O32(4-) in oxygenated aqueous solution. Addition of these polyoxometalate (POM) anions to TiO2 suspensions resulted in significant rate enhancement for DCB oxidation. Photodegradation kinetics exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
127
4
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(141 citation statements)
references
References 60 publications
5
127
4
5
Order By: Relevance
“…So heteropolyacids have been frequently used as photocatalysts in the oxidation or reduction of organic or inorganic compounds in water. Ozer has reported the use of heteropolyacids such as PW 12 [16], and another report also observed that the doping heteropolyacids into TiO 2 can increase eightfold in the apparent degradation rate of 1,2-dichlorobenzene compared to TiO 2 alone [17].…”
Section: Introductionmentioning
confidence: 99%
“…So heteropolyacids have been frequently used as photocatalysts in the oxidation or reduction of organic or inorganic compounds in water. Ozer has reported the use of heteropolyacids such as PW 12 [16], and another report also observed that the doping heteropolyacids into TiO 2 can increase eightfold in the apparent degradation rate of 1,2-dichlorobenzene compared to TiO 2 alone [17].…”
Section: Introductionmentioning
confidence: 99%
“…According to Yoon et al, the photoinduced charge-carrier generation at the HPA-TiO 2 heterojunction was very efficient and was also enhanced upon illumination of the HPA-incorporated TiO 2 with visible light as well as near-UV light. In an analogous way, Ozer et al [52] 40 . [54] HPAs as oxidants are more effective than O 2 to remove conduction band electrons from TiO 2 .…”
Section: Hpa Supported On Different Oxidesmentioning
confidence: 87%
“…[54] HPAs as oxidants are more effective than O 2 to remove conduction band electrons from TiO 2 . [52] Mixtures of H 3 PW 12 O 40 with commercial TiO 2 Degussa P25 were used for 2,4-dichlorophenol photocatalytic degradation in aqueous media. [55] H 3 PW 12 O 40 species on the surface of TiO 2 accelerated the hydroxylation of the substrate but not its mineralization, which was somewhat suppressed in the presence of the HPA.…”
Section: Hpa Supported On Different Oxidesmentioning
confidence: 99%
“…Holeelectron recombination is a serious problem for the development of photocatalytically based technologies, since it severely limits the achievable quantum yields. 12 However, there are some strategies to reduce electron-hole recombination rates and increase photocatalyst efficiency. A common method consists of the doping of titania with transition metal ions while maintaining a good control of the primary particle size to achieve nanoscale configurations of the catalysts.…”
Section: Introductionmentioning
confidence: 99%